Process Improvement Proposal Storage to Increase the Service Level Using Lean Warehousing in Commerce Companies - Gil-Goyzueta, Elmer Alfonso (2022)
This paper presents a proposal to improve the storage process using the Lean Warehousing, 5S, SLP, and PDCA tools to improve the indicator of perfect deliveries. Initially, a diagnosis of the current situation of the warehouse was executed, analyzing and collecting quantitative and qualitative information on the storage processes. The principal causes of the low service level were analyzed, and three main problems were identified as substantial causes, non-compliance with the quantities and items of the orders (53.54%), the delay of deliveries (24.8%), and the deterioration or obsolescence of stocks in the warehouse (23.82%). In order to reduce these deficiencies, improvements were proposed regarding the company's operational processes and policies, as well as modifications in the warehouse layout. In this way, unproductive times or overtime and the route of activities such as picking and storage will be reduced by 75%.